2014
DOI: 10.2478/s11535-014-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antimicrobial, antioxidative and anticholinesterase activity of Satureja Montana L. ssp montana essential oil

Abstract: Abstract:The present study investigates the chemical compositions of three Satureja montana L. ssp montana essential oils and correlates chemical variability with biological activities. GC/MS analysis showed that with an increase in altitude (100-500-800 m), a higher content of linalool, terpinen-4-ol and cis-sabinene hydrate was found, while the percentage of phenolic compounds, thymol and carvacrol decreased. Antimicrobial activity of the essential oils was tested against 7 fungal and 23 bacterial strains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 28 publications
2
31
0
1
Order By: Relevance
“…Winter savory honey is a very frequent ingredient in folk remedies known for their beneficial effects in the treatment of bronchitis. In addition, it is used as an antiseptic in gastrointestinal complaints, might be used as choleretic, digestive remedy, and in the treatment of premature ejaculation [14]. Wild savory is a medicinal and aromatic plant which essential oil commonly has application in the preparation of the aromatic water, especially in the mountainous areas of Turkey and in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Winter savory honey is a very frequent ingredient in folk remedies known for their beneficial effects in the treatment of bronchitis. In addition, it is used as an antiseptic in gastrointestinal complaints, might be used as choleretic, digestive remedy, and in the treatment of premature ejaculation [14]. Wild savory is a medicinal and aromatic plant which essential oil commonly has application in the preparation of the aromatic water, especially in the mountainous areas of Turkey and in the Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of phenolic compounds in these plants' essential oil might be responsible for their taste and fragrance. Winter savory has been known for its antimicrobial activity, probably due to the presence of monoterpene, alcohols and phenolic compounds, as stated in available literature data [14,15]. The use of wild savory in the Montenegro has been less frequent in comparison to above-mentioned areas where traditionally this plant has been well recognised.…”
Section: Introductionmentioning
confidence: 99%
“…The herb of S. montana contains essential oil [García-Rellán et al 2015], phenolic compounds and flavonoids [Hassanein et al 2014]. S. montana essential oil exhibits antibacterial [Miladi et al 2013, Mihajilov-Krstev et al 2014 and antioxidant activity [Miladi et al 2013]. The antioxidant activity of S. montana herb is probably attributable to the presence of phenolic compounds and flavonoids [Hassanein et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Damjanovic-Vratnica et al (2011) observed variability in composition of essential oil of S. montana wild collected in central part of Montenegro, depending on time of harvest; before flowering content of thymol was 37.4% and the second major constituent was carvacrol, 15.5%, while in the full flowering stage, thymol was 27.7%, but the second constituent was γ-terpinene, 8.7%. Mihajilov-Krstev et al (2014) in samples collected from Montenegro, reported differences in essential oil composition depending on altitude; contents of thymol and carvacrol were the highest at the lowest examined altitude (100 m a.s.l, near the Budva city), 24.7% and 15.2%, respectively. Difference in chemical composition of this oil further suggest that geo-climatic parameters of locality where this plant species is cultivated might affect content of the major oil constituents, as there were apparent differences in available literature data.…”
Section: Essential Oil Yield and Compositionmentioning
confidence: 93%